Breastfeeding based on Breastfeeding Self-efficacy and Social Support in Wonokromo Surabaya - Nisa, Fauziyatun; Damayanti, Nyoman; Suhariadi, Fendy; Anggasari, Yasi; Dewi, Ficky Erika; Arini, Diyah; Rahman, Firman Suryadi (Open Access Macedonian Journal of Medical Sciences, 2021)
A mother, who has low self-confidence in her ability to provide exclusive breastfeeding, supported by culture and myth, think when a baby cries it means that the baby is hungry and breast milk only is not enough. Therefore, a lot of mothers decided to give banana, porridge, honey, and other additional foods. This research aimed to determine the relationship between breastfeeding self-efficacy and social support with breastfeeding in Wonokromo, Surabaya. This research was conducted through analytical design using cross-sectional approach. The research samples involved were 112 mothers who had baby aged 6-12 months old. Among them, 106 mothers were chosen as research respondents using simple random sampling technique. The independent variable of this research was breastfeeding self-efficacy and social support, while the dependent variable was breastfeeding. Data were collected using a questionnaire, and then analyzed through Chi-Square test using SPSS program with the level of significance determined was α = 0.05. The results showed that most of the respondents had poor breastfeeding self-efficacy (77.4%) and low social support (51.9%), as well as did not exclusively breastfeed (66.9%). Based on the Chi-square test, the value obtained was ρ - 0.00 < α - 0.05, so H0 rejected, indicating that there was a relationship between breastfeeding self-efficacy and breastfeeding. Another value obtained was ρ - 0.00 < α - 0.05 so H0 rejected, which also means that there was a relationship between social support and breastfeeding. This outcome concluded that the better the breastfeeding self-efficacy and higher social support, the higher level of breastfeeding without additional food. Therefore, we suggested that health workers and the community will be able to motivate mothers and provide social support in terms of providing breast milk to babies without additional food.